Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.
Quadratic Equations (Quadratic Formula) by Rich Rollo
The Equation 5y 2  –8y  + 3 = 0
The Quadratic Formula x = -b  + b 2  –4ac 2a
Identify the Parts ay 2  + by + c = 0 5y 2  –8y + 3 = 0 Therefore in this case, a = 5, b = -8, and c = 3.
Step One Plug in the values of a, b, and c into the quadratic formula. x = -(-8)  + (-8) 2  –4(5)(3) 2(5)
Step Two Simplify all terms found within the radicand. x = -(-8)  + 64 –60 2(5) x = -(-8)  + 4 2(5)
Step 3 Simplify the remaining terms in the formula. x = -(-8)  + 4 2(5) x = 8  + 2 10
Step 4 Isolate the variable to find the solution set. x = 8  + 2 10 X = 8 + 2 X = 8 –2  10 10 = = 1 .6 &
Solution Set 1 and .6
Check the 1 st  Solution Check ………………………………………… 1 5y 2  –8y + 3 = 0 5(1) 2  –8(1) + 3 = 0 5 –8 + 3 = 0 True
Check the 2 nd  Solution Check ………………………………six-tenths. (.6) 5y 2  –8y + 3 = 0 5(.6) 2  –8(.6) + 3 = 0 1.8 –4.8 + 3 = 0 True
Therefore 1 and .6 is the solution set for 5y 2  –8y  + 3 = 0
Upcoming SlideShare
Loading in …5
×

Quadratic Equations (Quadratic Formula) Using PowerPoint

17,628 views

Published on

Quadratic Equations (Quadratic Formula) Using PowerPoint

  1. 1. Quadratic Equations (Quadratic Formula) by Rich Rollo
  2. 2. The Equation 5y 2 –8y + 3 = 0
  3. 3. The Quadratic Formula x = -b + b 2 –4ac 2a
  4. 4. Identify the Parts ay 2 + by + c = 0 5y 2 –8y + 3 = 0 Therefore in this case, a = 5, b = -8, and c = 3.
  5. 5. Step One Plug in the values of a, b, and c into the quadratic formula. x = -(-8) + (-8) 2 –4(5)(3) 2(5)
  6. 6. Step Two Simplify all terms found within the radicand. x = -(-8) + 64 –60 2(5) x = -(-8) + 4 2(5)
  7. 7. Step 3 Simplify the remaining terms in the formula. x = -(-8) + 4 2(5) x = 8 + 2 10
  8. 8. Step 4 Isolate the variable to find the solution set. x = 8 + 2 10 X = 8 + 2 X = 8 –2 10 10 = = 1 .6 &
  9. 9. Solution Set 1 and .6
  10. 10. Check the 1 st Solution Check ………………………………………… 1 5y 2 –8y + 3 = 0 5(1) 2 –8(1) + 3 = 0 5 –8 + 3 = 0 True
  11. 11. Check the 2 nd Solution Check ………………………………six-tenths. (.6) 5y 2 –8y + 3 = 0 5(.6) 2 –8(.6) + 3 = 0 1.8 –4.8 + 3 = 0 True
  12. 12. Therefore 1 and .6 is the solution set for 5y 2 –8y + 3 = 0

×